Pengaruh konsentrasi asam klorida dan metode ekstraksi microwave terhadap karakterisik kolagen tulang ikan tuna (Thunus sp) - Jariah; Marisa Rizky Hanivia (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
Indonesia still imports more than 6200 tons of collagen with the price reaching approximately 1. Therefore, domestic industrial developers are needed to produce collagen. Collagen itself is usually made from bone or skin raw materials from pigs or cows, but recently there are frequent infectious diseases from this livestock so raw materials from fisheries can overcome these problems to be used as materials for making collagen. Tuna fish bones have a high collagen protein content and can be used as an alternative raw material for collagen. The purpose of this study was to determine the characteristics of tuna bone collagen made by Factor I concentration of hydrochloric acid (1%,3%,5%) with factor II extraction time (30 minutes, 60 minutes, 90 minutes). This study uses a Completely Randomized Design (CRD). In the results of the study, the best treatment, namely the treatment of 5% hydrochloric acid concentration with an extraction time of 90 minutes, had a yield value of 21.05%, the water content of 2.69%, ash content of 0.27%, pH value of 7.23, viscosity value 3 .38cP and Color (L*) 75.31. Furthermore, the results of the FTIR analysis of Amide A, Amide B, Amide I, Amide II, and Amide III with absorption peaks in a row (3362.52 cm-1), (2935.25 cm-1), (1626.46cm-1 ),(1517,14cm-1),(1235.52cm-1)